2001
DOI: 10.1046/j.1471-4159.2001.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

(1R,3S)‐1‐Aminocyclopentane‐1,3‐dicarboxylic acid (RS‐ACPD) reduces intracellular glutamate levels in astrocytes

Abstract: Abstract(1/±)-1-Aminocyclopentane-trans-1,3-dicarboxylic acid (t-ACPD) is an equimolar mixture of two enantiomers: (1S,3R)-1-Aminocyclopentane-1,3-dicarboxylic acid (SR-ACPD) and 1R,3S-1-Aminocyclopentane-1,3-dicarboxylic acid (RS-ACPD). t-ACPD and SR-ACPD have been commonly used as agonists for metabotropic glutamate receptors (mGluR). Here we demonstrated that RS-ACPD, but not SR-ACPD, is transported into astrocytes with a K m of 6.51^2.38 mM and V max of 22.8^3.4 nmol/mg/min. This low-af®nity transport is Na Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Previous studies have showed that a significant increase in Glx was found in oligodendrogliomas and was used to discriminate them relative to low-grade astrocytomas (34). The increase in Glu that was observed in the Grade 3 glioma considered in our study is consistent with the observation that glioma cells may secrete Glu, resulting in an increase in extracellular Glu (35,36). Increased Glu could be also associated with inflammation in the peritumor tissues since activated microglia and brain macrophages express high affinity glutamate transporters (37) and stimulates tumor cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have showed that a significant increase in Glx was found in oligodendrogliomas and was used to discriminate them relative to low-grade astrocytomas (34). The increase in Glu that was observed in the Grade 3 glioma considered in our study is consistent with the observation that glioma cells may secrete Glu, resulting in an increase in extracellular Glu (35,36). Increased Glu could be also associated with inflammation in the peritumor tissues since activated microglia and brain macrophages express high affinity glutamate transporters (37) and stimulates tumor cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…High glucose may or may not influence experimental outcome, but diabetic complications are, nevertheless, a concern for astrocytes and neurons grown in high glucose, and it is important to re-evaluate the results of such studies (e.g. 20 mmol/l glucose: Ye et al, 2001, 2003, 2009; McCoy and Sontheimer, 2010; 25 mmol/l glucose: Sorg and Magistretti, 1991; Yu et al., 1993; Takahashi et al, 1995; Itoh et al, 2003; Pellerin and Magistretti, 2005, 1994; Chenal and Pellerin, 2007; and 50 mmol/l glucose: Bliss et al, 2004). Also, Methods sections in published studies sometimes only identify the ‘generic’ culture medium (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple amino acid concentrations (Arg, Asn, Asp, Gln, Glu, Gly, Ser, Tau, Thr) in the lyophilized heart extracts dissolved in 2 H2O were determined by HPLC. Amino acids were precolumn derivatized with o-phthalialdehyde (Sigma, St. Louis, MO), separated, and measured as previously described (38).…”
Section: Methodsmentioning
confidence: 99%